Water-based acrylic emulsified asphalt anticorrosive paint, preparation method of anticorrosive paint and preparation method of water-based acrylic emulsion
By using anionic emulsifiers in aqueous acrylic emulsions and controlling particle size, the compatibility problem between the acrylic anticorrosion coating system and asphalt is solved, and the stability and performance of the coating are improved.
Patent Information
- Application Number
- CN202411842402.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-02-28
AI Technical Summary
The existing acrylic anticorrosion coating system introduces asphalt with acrylic emulsions, and layering will occur when thermal storage of acrylic emulsions and emulsified asphalt is carried out for a long time.
By using anionic emulsifier in the aqueous acrylic emulsion, it interacts with the carboxyl group of the acrylic monomer, achieving good emulsification effect and compatibility, and controlling the particle size of the aqueous acrylic emulsion to be within the range of 100 nm to 140 nm.
It effectively reduces the interface energy between anionic emulsified bitumen and aqueous acrylic emulsion, prevents layering, improves the storage stability of the paint, and enhances its water, salt spray, impact resistance and bending properties.
Smart Images

Figure CN119529674A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of anti-corrosion coatings, and in particular to a water-based acrylic emulsified asphalt anti-corrosion coating, a preparation method of the anti-corrosion coating, and a preparation method of an acrylic emulsion. Background Art
[0002] At present, the anti-corrosion coating obtained by single-component acrylic anti-corrosion coating has many shortcomings, such as low solid content and the hydrophilic groups of the resin molecules themselves can allow air and water to flow freely, resulting in poor anti-corrosion effect of the coating layer. Asphalt is a low-cost material with good flexibility and hydrophobicity that can effectively improve the anti-corrosion performance of the anti-corrosion coating. However, the introduction of asphalt into the acrylic anti-corrosion coating system has problems with compatibility with acrylic emulsion. Long-term hot storage of acrylic emulsion and emulsified asphalt will cause stratification.
[0003] It can be seen that the existing technology still needs to be improved and enhanced. Summary of the invention
[0004] The purpose of the present invention is to provide a water-based acrylic composite latex, a water-based propionate composite latex and a preparation method, aiming to solve the problem of compatibility between asphalt and acrylic emulsion when the existing acrylic anti-corrosion coating system is introduced, and the problem of stratification of acrylic emulsion and emulsified asphalt during long-term hot storage.
[0005] To achieve the above object, the solution provided by the present invention is:
[0006] The present invention provides a water-based acrylic emulsified asphalt anti-corrosion coating, comprising the following components in parts by weight:
[0007] 30-40 parts of anionic emulsified asphalt, 20-30 parts of water-based acrylic emulsion, 18-22 parts of filler, 14-16 parts of deionized water, 1.5 parts of film-forming aid, 1 part of flash rust inhibitor, 0.5 parts of thickener, 0.5 parts of dispersant, 0.3 parts of neutralizer, 0.2 parts of leveling agent, 0.1 parts of bentonite, and 0.1 parts of defoamer A;
[0008] The aqueous acrylic emulsion comprises the following components in parts by weight:
[0009] 50-51.16 parts of deionized water, 18-22 parts of styrene, 6-10 parts of methyl methacrylate, 3-6 parts of isooctyl acrylate, 3-6 parts of butyl acrylate, 3-6 parts of methacrylic acid, 1.4 parts of pH adjuster, 1 part of acrylic acid, 1 part of glycidyl methacrylate, 0.64-0.66 parts of anionic emulsifier, 0.4 parts of initiator, 0.1 parts of pH buffer, 0.02 parts of oxidant, 0.02 parts of reducing agent, 0.15 parts of wetting agent, 0.1 parts of preservative, and 0.05 parts of defoaming agent B.
[0010] Optionally, the anionic emulsifier includes at least one of a sulfonate anionic emulsifier and a sulfate anionic emulsifier.
[0011] Optionally, the sulfonate anionic emulsifier includes at least one of sodium dodecylbenzenesulfonate and ammonium dodecylbenzenesulfonate.
[0012] Optionally, the film-forming aid includes at least one of lauryl alcohol ester, ethylene glycol monobutyl ether, and propylene glycol butyl ether.
[0013] Optionally, the filler includes at least one of heavy calcium, titanium dioxide, and barium sulfate.
[0014] Optionally, the defoaming agent B includes a polyether defoaming agent, the wetting agent includes lauryl alcohol polyoxyethylene ether, and the preservative includes a Kathon preservative.
[0015] Optionally, the pH regulator includes ammonia water with a mass percentage concentration of 48-50%, and the pH buffer includes at least one of sodium bicarbonate and sodium carbonate.
[0016] Optionally, the initiator includes at least one of sodium persulfate, potassium persulfate, and ammonium persulfate, the oxidant includes at least one of tert-butyl hydroperoxide and hydrogen peroxide, and the reducing agent includes at least one of sodium pyrosulfite and ascorbic acid.
[0017] The present invention provides a method for preparing an aqueous acrylic emulsion, comprising the following steps:
[0018] S001. First, add 18 parts of deionized water to the emulsification tank, then add acrylic acid, methacrylic acid, pH buffer and 0.6 parts of anionic emulsifier to the emulsification tank, adjust the stirring speed to 200-300 rpm / min, and continue stirring for 8-10 minutes;
[0019] S002. After the stirring in step S001 is completed, the stirring speed is adjusted to 300-400 rpm / min, and butyl propylene, methyl methacrylate, styrene, isooctyl acrylate, and glycidyl methacrylate are added to the emulsification tank in sequence, and stirring is continued until a smooth and stable pre-emulsion is obtained;
[0020] S003. 0.1 parts of the initiator were added to 0.9 parts of deionized water and fully dissolved to obtain an initiator solution A;
[0021] S004. 0.3 parts of the initiator were added to 5.7 parts of deionized water and fully dissolved to obtain an initiator solution B;
[0022] S005. 0.02 parts of the oxidant are added to 0.18 parts of deionized water and fully dissolved to obtain an oxidant solution;
[0023] S006. 0.02 parts of the reducing agent are added to 0.18 parts of deionized water and fully dissolved to obtain a reducing agent solution;
[0024] S007. Add 25 parts of deionized water to the reactor, heat the reactor to 65-75°C, add 0.04-0.06 parts of anionic emulsifier to the reactor, and stir for 8-12 minutes;
[0025] S008. After the stirring in step S007 is completed, the reactor is heated to 85 to 87°C, and then 5% of the total weight of the pre-emulsion is added to the reactor, and the initiator solution A is immediately added for seeding;
[0026] S009. Observe the temperature of the reactor. When the temperature of the reactor is 88°C, the remaining pre-emulsion and initiator solution B are added dropwise to the reactor. During the addition, the temperature of the reactor is controlled at 85 to 88°C.
[0027] S010. After the initiator solution B and the pre-emulsion are added, the reactor is kept warm for 58 to 62 minutes. After the insulation is completed, the reactor is cooled to 65 to 70°C, and then the oxidant solution and the reducing agent solution are added simultaneously;
[0028] S011. After the oxidant solution and the reductant solution are added dropwise, the reactor is kept warm for 8 to 12 minutes. After the insulation is completed, the reactor is cooled to 50°C, and then a pH adjuster, 1.0 to 2.0 parts of deionized water, a wetting agent, a preservative, and a defoaming agent are added in sequence. The mixture is stirred for 4 to 6 minutes and then filtered to obtain an aqueous acrylic emulsion.
[0029] The present invention also provides a method for preparing a water-based acrylic emulsified asphalt anticorrosive coating, comprising the following steps:
[0030] T001. Add deionized water, neutralizer, dispersant, defoamer and filler to the grinder in order, grind until the fineness of the mixed liquid is less than 30um, and then add water-based acrylic emulsion and film-forming aid to the mixed liquid;
[0031] T002. After the water-based acrylic emulsion and the film-forming aid are added to the mixture, the mixture is stirred in a high-speed disperser for 10 to 12 minutes, and the speed of the high-speed stirrer is controlled at 780 to 820 rpm / min;
[0032] T003. After the stirring of step T002 is completed, continue to add anionic emulsified asphalt, leveling agent, anti-rust agent, and thickener to the mixed liquid. The speed of the high-speed mixer is controlled at 1500-1800 rpm / min. After stirring for 18-20 minutes, a water-based acrylic emulsified asphalt anti-corrosion coating is obtained.
[0033] The beneficial effect of the present invention is as follows: the present invention provides a water-based acrylic emulsified asphalt anti-corrosion coating, which uses an anionic emulsifier in the water-based acrylic emulsion so that the hydrophilic group of the anionic emulsifier can interact with the carboxyl group of the acrylic monomer, such as forming a hydrogen bond or an ion pair. This interaction helps the anionic emulsifier to better adsorb on the surface of the acrylic monomer, thereby achieving a good emulsification effect, so that the water-based acrylic emulsion and the anionic emulsified asphalt with extremely weak polarity have very good compatibility, and can effectively reduce the interfacial energy between the anionic emulsified asphalt and the water-based acrylic emulsion. When the acrylic anti-corrosion coating is stored for a long time, the acrylic emulsion and the emulsified asphalt will not be stratified.
[0034] The present invention also provides a method for preparing a water-based acrylic emulsion. By controlling the amount of anionic emulsifier used during the polymerization reaction of acrylic acid monomers, the particle size of the prepared water-based acrylic emulsion can be controlled, so that the particle size range of the water-based acrylic emulsion can be 100nm to 140nm. The water-based acrylic emulsion has better compatibility with the anionic emulsifier, so that the water-based acrylic emulsified asphalt anti-corrosion coating is stable in storage and will not delaminate. At the same time, the water-based acrylic emulsified asphalt anti-corrosion coating has excellent water resistance, salt spray resistance, impact resistance and bending performance.
[0035] The present invention also provides a method for preparing a water-based acrylic emulsified asphalt anti-corrosion coating. The preparation method is simple and efficient, and the equipment used in the preparation method is easy to deploy, and can be widely promoted in the anti-corrosion coating industry. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 The present invention is a flow chart of a method for preparing a water-based acrylic emulsified asphalt anti-corrosion coating. DETAILED DESCRIPTION
[0037] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] The present invention provides a water-based acrylic emulsified asphalt anti-corrosion coating, comprising the following components in parts by weight:
[0039] 30-40 parts of anionic emulsified asphalt, 20-30 parts of water-based acrylic emulsion, 18-22 parts of filler, 14-16 parts of deionized water, 1.5 parts of film-forming aid, 1 part of anti-flash rust agent, 0.5 parts of thickener, 0.5 parts of dispersant, 0.3 parts of neutralizer, 0.2 parts of leveling agent, 0.1 parts of bentonite, and 0.1 parts of defoaming agent A.
[0040] In the composition of the above-mentioned water-based acrylic emulsified asphalt anticorrosive coating, the acrylic copolymer in the water-based acrylic emulsion helps the flow and wettability of the molecular chain on the surface of the substrate, so that the anticorrosive coating and the substrate molecules are in close contact, and the adhesion of the anticorrosive coating to the substrate is improved; in addition, the water-based acrylic emulsion itself has excellent wettability, which can prevent water molecules from penetrating into the substrate after the paint film dries, achieving a waterproof and moisture-proof effect. The anionic emulsified asphalt has good flexibility and hydrophobicity, and can effectively improve the anticorrosive performance of the anticorrosive coating.
[0041] In the composition of the above-mentioned water-based acrylic emulsified asphalt anticorrosive coating, the filler can increase the consistency of the anticorrosive coating, increase the solid content of the coating, and make the anticorrosive coating more solid and wear-resistant. At the same time, the introduction of the filler can improve the construction performance of the coating, reduce the cost and improve the weather resistance of the anticorrosive coating. The introduction of the bentonite can prevent the sedimentation of the filler, so that the physical and chemical properties of the anticorrosive coating will not be affected.
[0042] In the composition of the above-mentioned water-based acrylic emulsified asphalt anti-corrosion coating, the water-based acrylic emulsion comprises the following components in parts by weight:
[0043] 50-51.16 parts of deionized water, 18-22 parts of styrene, 6-10 parts of methyl methacrylate, 3-6 parts of isooctyl acrylate, 3-6 parts of butyl acrylate, 3-6 parts of methacrylic acid, 1.4 parts of pH adjuster, 1 part of acrylic acid, 1 part of glycidyl methacrylate, 0.64-0.66 parts of anionic emulsifier, 0.4 parts of initiator, 0.1 parts of pH buffer, 0.02 parts of oxidant, 0.02 parts of reducing agent, 0.15 parts of wetting agent, 0.1 parts of preservative, and 0.05 parts of defoaming agent B.
[0044] Among them, the styrene and methyl methacrylate are hard monomers, which can give the water-based acrylic emulsion and the anti-corrosion coating containing the water-based acrylic emulsion certain water resistance, salt resistance and gloss. Isooctyl acrylate and butyl acrylate are soft monomers, which can give the emulsion and the anti-corrosion coating good flexibility and elasticity. Methacrylic acid, acrylic acid, and glycidyl methacrylate are all functional monomers, which can provide hydrogen bonds for the water-based acrylic emulsion, so that hydrogen bonds are formed between the anti-corrosion coating containing the water-based acrylic emulsion and the substrate, thereby improving the adhesion between the anti-corrosion coating and the substrate.
[0045] The anionic emulsifier has good compatibility with acrylic monomers (the above-mentioned soft and hard monomers and functional monomers). Acrylic monomers are unsaturated compounds containing carboxyl groups (-COOH) and have certain acidity, and the hydrophilic groups of the anionic emulsifier can interact with the carboxyl groups of the acrylic monomers, such as forming hydrogen bonds or ion pairs. This interaction helps the anionic emulsifier to be better adsorbed on the surface of the acrylic monomer, thereby achieving a good emulsification effect, so that the water-based acrylic emulsion has very good compatibility with the anionic emulsified asphalt with extremely weak polarity, and can effectively reduce the interfacial energy between the anionic emulsified asphalt and the water-based acrylic emulsion. When the acrylic anti-corrosion coating is stored for a long time, the acrylic emulsion and the emulsified asphalt will not be stratified.
[0046] Optionally, the anionic emulsifier includes at least one of a sulfonate anionic emulsifier and a sulfate anionic emulsifier. The anionic emulsifier has a hydrophilic sulfonic acid group and a hydrophilic sulfuric acid group, which can interact with the carboxyl group of the acrylic acid monomer, and help the emulsifier to better adsorb on the surface of the acrylic acid monomer.
[0047] Optionally, the sulfonate anionic emulsifier includes at least one of sodium dodecylbenzene sulfonate and ammonium dodecylbenzene sulfonate. Preferably, the sulfonate anionic emulsifier is sodium dodecylbenzene sulfonate, which not only can achieve a good emulsification effect, but also has a solubilizing effect, thereby forming a stable aqueous acrylic emulsion.
[0048] Optionally, the film-forming aid includes at least one of lauryl alcohol ester, ethylene glycol monobutyl ether, and propylene glycol butyl ether.
[0049] Optionally, the filler includes at least one of heavy calcium, titanium dioxide, and barium sulfate.
[0050] Optionally, the anti-flash rust agent is composed of Raybo 60 anti-flash rust agent, the thickener is RM-8W thickener, the dispersant is OROTAN 731A dispersant, the neutralizer is AMP-95 amine neutralizer, the leveling agent is Digo 4100 leveling agent, and the defoamer A is BYK-024 defoamer.
[0051] Optionally, the anionic emulsified asphalt is selected from Kunlun brand anionic emulsified asphalt.
[0052] Optionally, the defoaming agent B includes a polyether defoaming agent, the wetting agent includes lauryl alcohol polyoxyethylene ether, and the preservative includes a Kathon preservative.
[0053] Optionally, the pH regulator includes ammonia water with a mass percentage concentration of 48-50%, and the pH buffer includes at least one of sodium bicarbonate and sodium carbonate.
[0054] Optionally, the initiator includes at least one of sodium persulfate, potassium persulfate, and ammonium persulfate, the oxidant includes at least one of tert-butyl hydroperoxide and hydrogen peroxide, and the reducing agent includes at least one of sodium pyrosulfite and ascorbic acid. The oxidant and reducing agent are used to remove unreacted residual monomers during the preparation of the aqueous acrylic emulsion.
[0055] The present invention provides a method for preparing an acrylic emulsion, comprising the following steps: S001. firstly adding 18 parts of deionized water into an emulsifying tank, then adding acrylic acid, methacrylic acid, a pH buffer and 0.6 parts of anionic emulsifier into the emulsifying tank, adjusting the stirring speed to 200-300 rpm / min, and continuously stirring for 8-10 minutes;
[0056] S002. After the stirring in step S001 is completed, the stirring speed is adjusted to 300-400 rpm / min, and butyl propylene, methyl methacrylate, styrene, isooctyl acrylate, and glycidyl methacrylate are added to the emulsification tank in sequence, and stirring is continued until a smooth and stable pre-emulsion is obtained;
[0057] S003. 0.1 parts of the initiator were added to 0.9 parts of deionized water and fully dissolved to obtain an initiator solution A;
[0058] S004. 0.3 parts of the initiator were added to 5.7 parts of deionized water and fully dissolved to obtain an initiator solution B;
[0059] S005. 0.02 parts of the oxidant are added to 0.18 parts of deionized water and fully dissolved to obtain an oxidant solution;
[0060] S006. 0.02 parts of the reducing agent are added to 0.18 parts of deionized water and fully dissolved to obtain a reducing agent solution;
[0061] S007. Add 25 parts of deionized water to the reactor, heat the reactor to 65-75°C, add 0.04-0.06 parts of anionic emulsifier to the reactor, and stir for 8-12 minutes;
[0062] S008. After the stirring in step S007 is completed, the reactor is heated to 85 to 87°C, and then 5% of the total weight of the pre-emulsion is added to the reactor, and the initiator solution A is immediately added for seeding;
[0063] S009. Observe the temperature of the reactor. When the temperature of the reactor is 88°C, the remaining pre-emulsion and initiator solution B are added dropwise to the reactor. During the addition, the temperature of the reactor is controlled at 85 to 88°C.
[0064] S010. After the initiator solution B and the pre-emulsion are added, the reactor is kept warm for 58 to 62 minutes. After the insulation is completed, the reactor is cooled to 65 to 70°C, and then the oxidant solution and the reducing agent solution are added simultaneously;
[0065] S011. After the oxidant solution and the reductant solution are added dropwise, the reactor is kept warm for 8 to 12 minutes. After the insulation is completed, the reactor is cooled to 50°C, and then a pH adjuster, 1.0 to 2.0 parts of deionized water, a wetting agent, a preservative, and a defoaming agent are added in sequence. The mixture is stirred for 4 to 6 minutes and then filtered to obtain an aqueous acrylic emulsion.
[0066] The present invention finds that when the particle size of the aqueous acrylic emulsion and the particle size of the anionic emulsified asphalt are not much different, the aqueous acrylic emulsion will be more evenly dispersed. When the particle size of the acrylic emulsion is in the range of 100nm to 140nm, when mixed with the anionic emulsified asphalt, the aqueous acrylic emulsion particle size of 100nm to 140nm helps to enhance the interfacial bonding force between the emulsion particles and the asphalt particles. At this time, the emulsion particles can be tightly attached to the surface of the asphalt particles, and the connection between the two is strengthened by chemical bonding, physical adsorption, etc.
[0067] When the particle size of the water-based acrylic emulsion is less than 100nm, the specific surface area of the emulsion particles will be very large. Although it is beneficial to the contact between the emulsion particles and the components in the emulsified asphalt to a certain extent, the stability of the emulsion particles themselves may be too high due to the small particle size of the emulsion particles. As a result, when the emulsion particles are mixed with the anionic emulsified asphalt, they cannot break the original stable state and penetrate with the asphalt particles. Moreover, when the particle size of the emulsion particles is too small, the emulsion particles are prone to agglomeration, especially when mixed with a complex system such as anionic emulsified asphalt. The tiny emulsion particles are easily aggregated due to factors such as electrostatic effects, which is not conducive to compatibility with anionic emulsified asphalt.
[0068] When the particle size of the water-based acrylic emulsion is greater than 140nm, the paint film formed by the large-size emulsion particles is relatively less dense, and there will be more pores and defects in the paint film, which will reduce the barrier properties of the paint film, such as the barrier ability to water, oxygen, chemicals, etc., thereby affecting the protection, adhesion and other properties of the anti-corrosion coating.
[0069] In the preparation method of the acrylic emulsion provided by the present invention, the amount of the anionic emulsifier used during the polymerization reaction of the acrylic monomer is controlled (in step S007), so that the particle size of the prepared aqueous acrylic emulsion can be controlled, so that the particle size range of the aqueous acrylic emulsion can be 100nm to 140nm, and the aqueous acrylic emulsion has better compatibility with the anionic emulsifier, so that the aqueous acrylic emulsified asphalt anti-corrosion coating is stable in storage and will not delaminate, and the aqueous acrylic emulsified asphalt anti-corrosion coating has excellent water resistance, salt spray resistance, impact resistance and bending performance.
[0070] The present invention also provides a method for preparing a water-based acrylic emulsified asphalt anticorrosive coating, comprising the following steps:
[0071] T001. Add deionized water, neutralizer, dispersant, defoamer and filler to the grinder in order, grind until the fineness of the mixed liquid is less than 30um, and then add water-based acrylic emulsion and film-forming aid to the mixed liquid;
[0072] T002. After the water-based acrylic emulsion and the film-forming aid are added to the mixture, the mixture is stirred in a high-speed disperser for 10 to 12 minutes, and the speed of the high-speed stirrer is controlled at 780 to 820 rpm / min;
[0073] T003. After the stirring of step T002 is completed, continue to add anionic emulsified asphalt, leveling agent, anti-rust agent, and thickener to the mixed liquid. The speed of the high-speed mixer is controlled at 1500-1800 rpm / min. After stirring for 18-20 minutes, a water-based acrylic emulsified asphalt anti-corrosion coating is obtained.
[0074] The preparation method of the water-based acrylic emulsified asphalt anti-corrosion coating provided by the present invention is simple and efficient; the equipment used in the preparation method is easy to deploy, and can be widely promoted in the anti-corrosion coating industry.
[0075] In order to further illustrate the water-based acrylic emulsified asphalt anti-corrosion coating, the preparation method of the anti-corrosion coating, and the preparation method of the acrylic emulsion provided by the present invention, the following examples and comparative examples are provided.
[0076] Example 1, Example 2, Example 3, Comparative Example 1 and Comparative Example 2 provide a water-based acrylic emulsified asphalt anti-corrosion coating, and the weight composition of the water-based acrylic emulsified asphalt anti-corrosion coating is shown in Table 1 below.
[0077] Table 1:
[0078]
[0079]
[0080] In Table 1, the aqueous acrylic emulsion comprises the following components in parts by weight:
[0081] 51.11 parts of deionized water, 20 parts of styrene, 8 parts of methyl methacrylate, 5 parts of isooctyl acrylate, 5 parts of butyl acrylate, 5 parts of methacrylic acid, 1.4 parts of 50% ammonia water (pH adjuster), 1 part of acrylic acid, 1 part of glycidyl methacrylate, 0.65 parts of sodium dodecylbenzene sulfonate (anionic emulsifier), 0.4 parts of sodium persulfate (initiator), 0.1 parts of sodium bicarbonate (pH buffer), 0.02 parts of tert-butyl hydroperoxide (oxidant), 0.02 parts of sodium pyrosulfite (reducing agent), 0.15 parts of lauryl alcohol polyoxyethylene ether (wetting agent), 0.1 parts of Kathon preservative (preservative), 0.05 parts of polyether defoamer (defoamer B)
[0082] In addition, Example 1 also provides a method for preparing an aqueous acrylic emulsion. Example 2, Example 3, Comparative Example 1 and Comparative Example 2 provide the same method for preparing an aqueous acrylic emulsion as Example 1. The specific preparation method includes the following steps:
[0083] The present invention provides a method for preparing an acrylic emulsion, comprising the following steps: S001. firstly adding 18 parts of deionized water into an emulsifying tank, then adding acrylic acid, methacrylic acid, a pH buffer and 0.6 parts of anionic emulsifier into the emulsifying tank, adjusting the stirring speed to 200-300 rpm / min, and continuously stirring for 8-10 minutes;
[0084] S002. After the stirring in step S001 is completed, the stirring speed is adjusted to 300-400 rpm / min, and butyl propylene, methyl methacrylate, styrene, isooctyl acrylate, and glycidyl methacrylate are added to the emulsification tank in sequence, and the stirring is continued for more than 30 minutes until a fine and stable pre-emulsion is obtained. During the stirring process, the temperature of the emulsification tank is maintained below 40°C to prevent the pre-emulsion from self-polymerization;
[0085] S003. 0.1 parts of the initiator were added to 0.9 parts of deionized water and fully dissolved to obtain an initiator solution A;
[0086] S004. 0.3 parts of the initiator were added to 5.7 parts of deionized water and fully dissolved to obtain an initiator solution B;
[0087] S005. 0.02 parts of the oxidant are added to 0.18 parts of deionized water and fully dissolved to obtain an oxidant solution;
[0088] S006. 0.02 parts of the reducing agent are added to 0.18 parts of deionized water and fully dissolved to obtain a reducing agent solution;
[0089] S007. Add 25 parts of deionized water to the reactor, heat the reactor to 65-75°C, add 0.04-0.06 parts of anionic emulsifier to the reactor, and stir for 8-12 minutes;
[0090] S008. After the stirring in step S007 is completed, the reactor is heated to 85 to 87°C, and then 5% of the total weight of the pre-emulsion is added to the reactor, and the initiator solution A is immediately added for seeding;
[0091] S009. Observe the temperature of the reactor. When the temperature of the reactor is 88°C, the remaining pre-emulsion and initiator solution B are added dropwise to the reactor. During the addition, the temperature of the reactor is controlled at 85 to 88°C.
[0092] S010. After the initiator solution B and the pre-emulsion are added, the reactor is kept warm for 58 to 62 minutes. After the insulation is completed, the reactor is cooled to 65 to 70°C, and then the oxidant solution and the reducing agent solution are added simultaneously;
[0093] S011. After the oxidant solution and the reductant solution are added dropwise, the reactor is kept warm for 8 to 12 minutes. After the insulation is completed, the reactor is cooled to 50°C, and then a pH adjuster, 1.15 parts of deionized water, a wetting agent, a preservative, and a defoaming agent are added in sequence. After stirring for 4 to 6 minutes, the aqueous acrylic emulsion is filtered to obtain a particle size range of 100 to 140 nm, a pH of 7.0 to 8.0, and a solid content of 45.5% to 46.5%.
[0094] Comparative Examples 3 and 4 respectively provide a water-based acrylic emulsified asphalt anti-corrosion coating, and the weight compositions of the water-based acrylic emulsified asphalt anti-corrosion coatings provided by Comparative Examples 3 and 4 are the same as the weight compositions of the water-based acrylic emulsified asphalt anti-corrosion coatings provided by Example 3 in Table 1. However, the weight compositions of the aqueous acrylic emulsions in the water-based acrylic emulsions in the water-based acrylic emulsions provided by Comparative Examples 3 and 4 are different from the weight compositions of the aqueous acrylic emulsions used in Example 3.
[0095] Specifically, Comparative Example 3 uses an aqueous acrylic emulsion comprising the following components in parts by weight:
[0096] 50.045 parts of deionized water, 20 parts of styrene, 8 parts of methyl methacrylate, 5 parts of isooctyl acrylate, 5 parts of butyl acrylate, 5 parts of methacrylic acid, 1.4 parts of 50% ammonia water (pH adjuster), 1 part of acrylic acid, 1 part of glycidyl methacrylate, 0.68 parts of sodium dodecylbenzene sulfonate (anionic emulsifier), 0.4 parts of sodium persulfate (initiator), 0.1 parts of sodium bicarbonate (pH buffer), 0.02 parts of tert-butyl hydroperoxide (oxidant), 0.02 parts of sodium pyrosulfite (reducing agent), 0.15 parts of lauryl alcohol polyoxyethylene ether (wetting agent), 0.1 parts of Kathon preservative (preservative), and 0.05 parts of polyether defoamer (defoamer B).
[0097] Comparative Example 3 also provides a method for preparing an aqueous acrylic emulsion. Except for steps S007 and S011, the remaining steps are the same as those of Example 1. Specifically, in step S007, the amount of anionic emulsifier used is 0.08 parts, and in step S011, the amount of deionized water used is 0.085 parts. The particle size range of the aqueous acrylic emulsion prepared by the preparation method is 70 to 100 nm, the pH of the aqueous acrylic emulsion is 7.0 to 8.0, and the solid content is 45.5% to 46.5%.
[0098] Specifically, the aqueous acrylic emulsion used in Comparative Document 4 comprises the following components in parts by weight:
[0099] 51.26 parts of deionized water, 20 parts of styrene, 8 parts of methyl methacrylate, 5 parts of isooctyl acrylate, 5 parts of butyl acrylate, 5 parts of methacrylic acid, 1.4 parts of 50% ammonia water (pH adjuster), 1 part of acrylic acid, 1 part of glycidyl methacrylate, 0.635 parts of sodium dodecylbenzene sulfonate (anionic emulsifier), 0.4 parts of sodium persulfate (initiator), 0.1 parts of sodium bicarbonate (pH buffer), 0.02 parts of tert-butyl hydroperoxide (oxidant), 0.02 parts of sodium pyrosulfite (reducing agent), 0.15 parts of lauryl alcohol polyoxyethylene ether (wetting agent), 0.1 parts of Kathon preservative (preservative), and 0.05 parts of polyether defoamer (defoamer B).
[0100] Comparative Example 4 also provides a method for preparing an aqueous acrylic emulsion. Except for steps S007 and S011, the remaining steps are the same as those of Example 1. Specifically, in step S007, the amount of anionic emulsifier used is 0.635 parts, and in step S011, the amount of deionized water used is 1.3 parts. The particle size of the aqueous acrylic emulsion prepared by the preparation method ranges from 140 to 170 nm, the pH of the aqueous acrylic emulsion is 7.0 to 8.0, and the solid content is 45.5% to 46.5%.
[0101] The performance of the water-based acrylic emulsified asphalt anticorrosive coatings provided in Examples 1 to 3 and Comparative Examples 1 to 4 was tested, specifically:
[0102] Test the thermal storage stability of anticorrosive coatings according to the standard "HG / T4758-2014 Water-based acrylic resin coatings" (50±2℃, 7d);
[0103] Test the surface drying and actual drying time of anti-corrosion coatings according to the standard "GB / T1728-2020 Determination of Drying Time of Paint Film and Putty Film";
[0104] Test the impact resistance of anti-corrosion coatings according to the standard "GB / T1732-2020 Paint film impact resistance test";
[0105] Test the anti-cracking or peeling performance of anti-corrosion coatings according to the standard "GB / T6742-2008 Paint and Varnish Bending Test (Cylindrical Mandrel)";
[0106] Evaluate the adhesion of anti-corrosion coatings according to the standard "GB / T6742-2007 Paint and Varnish Cross-cut Test";
[0107] Test the water resistance of anti-corrosion coatings according to the standard "GB / T1733-1993 Determination of water resistance of paint film";
[0108] The neutral salt spray resistance of anti-corrosion coatings is tested according to the standard "GB / T1771-2007 Determination of neutral salt spray resistance of paints and varnishes".
[0109] The hardness of the anti-corrosion coating formed by the anti-corrosion coating is tested according to the standard "GB / T6739-2022 Determination of paint film hardness by pencil method for paints and varnishes".
[0110] The test results are shown in Tables 2 and 3 below respectively.
[0111] Table 2
[0112]
[0113] It can be seen from Table 2 that the hardness, adhesion, water and salt spray resistance of the water-based acrylic emulsified asphalt anticorrosive coatings prepared in Examples 1-3 fully meet the requirements of the standard. It can be concluded from Table 2 that when the amount of water-based acrylic emulsion is reduced (Comparative Example 1) and the amount of emulsified asphalt is increased, the thermal storage stability and hardness performance decrease, because emulsified asphalt is a colloid system, and excessive addition of emulsified asphalt will make the coating system complicated and the interaction between the components will become out of control, that is, the coating system may experience demulsification, stratification, etc. The hardness decreases because the main component of emulsified asphalt is asphalt, which is relatively soft. When mixed with water-based acrylic acid, it will soften the rigid structure of the water-based acrylic emulsion film. However, when the amount of water-based acrylic emulsion increases (Comparative Example 2) and the amount of emulsified asphalt decreases, the water resistance, salt spray resistance and other properties decrease. This is because asphaltene, the main component of asphalt in emulsified asphalt, is a substance that can resist chemical corrosion. When the amount of emulsified asphalt is small, the anti-corrosion layer formed in the coating system is not complete or thick enough. Under the salt spray conditions of the test, salt can easily penetrate the anti-corrosion layer to reach the inside and cause rust, resulting in a decrease in the salt spray resistance of the coating. At the same time, asphalt is a hydrophobic material, and there are tiny gaps in the film formation of the water-based acrylic emulsion itself. The addition of emulsified asphalt can effectively fill these gaps, making it difficult for water molecules to pass through the protective layer and enter the interior of the material. When the amount of emulsified asphalt is reduced, these gaps are insufficiently filled, and water molecules may penetrate the coating, causing blistering and other adverse phenomena.
[0114] Table 3:
[0115]
[0116] It can be seen from Table 3 above that when the particle size of the aqueous acrylic emulsion is less than 100 nm (Comparative Example 3), the emulsion particles are prone to agglomeration, especially when mixed with a complex system such as anionic emulsified asphalt, the tiny emulsion particles are easily aggregated due to factors such as electrostatic effects, which is not conducive to compatibility with anionic emulsified asphalt. Therefore, the storage stability of the aqueous acrylic emulsified asphalt anticorrosive coating provided by Comparative Example 3 is not as good as that of Example 3. When the particle size of the aqueous acrylic emulsion is greater than 140 nm, the paint film formed by the large-size emulsion particles is relatively less dense, and there will be more pores and defects in the paint film, which will reduce the barrier properties of the paint film, such as the barrier capacity to water, oxygen, chemicals, etc., thereby affecting the protection, adhesion and other properties of the anticorrosive coating, which can also be reflected from the water resistance and salt spray resistance test results of Comparative Example 4 in Table 3 above.
[0117] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification and drawings under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. A water-based acrylic emulsified asphalt anti-corrosion coating, characterized in that: The invention comprises the following components in parts by weight: 30-40 parts of anionic emulsified asphalt, 20-30 parts of water-based acrylic emulsion, 18-22 parts of filler, 14-16 parts of deionized water, 1.5 parts of film-forming aid, 1 part of flash rust preventer, 0.5 parts of thickener, 0.5 parts of dispersant, 0.3 parts of neutralizer, 0.2 parts of leveling agent, 0.1 parts of bentonite and 0.1 parts of defoamer A; The aqueous acrylic emulsion comprises the following components in parts by weight: 50-51.16 parts of deionized water, 18-22 parts of styrene, 6-10 parts of methyl methacrylate, 3-6 parts of isooctyl acrylate, 3-6 parts of butyl acrylate, 3-6 parts of methacrylic acid, 1.4 parts of pH adjuster, 1 part of acrylic acid, 1 part of glycidyl methacrylate, 0.64-0.66 parts of anionic emulsifier, 0.4 parts of initiator, 0.1 parts of pH buffer, 0.02 parts of oxidant, 0.02 parts of reducing agent, 0.15 parts of wetting agent, 0.1 parts of preservative, and 0.05 parts of defoaming agent B.
2. The water-based acrylic emulsified asphalt anticorrosive coating according to claim 1, characterized in that: The anionic emulsifier includes at least one of a sulfonate anionic emulsifier and a sulfate anionic emulsifier.
3. The water-based acrylic emulsified asphalt anticorrosive coating according to claim 2, characterized in that: The sulfonate anionic emulsifier includes at least one of sodium dodecylbenzene sulfonate and ammonium dodecylbenzene sulfonate.
4. The water-based acrylic emulsified asphalt anticorrosive coating according to claim 1, characterized in that: The film-forming aid includes at least one of lauryl alcohol ester, ethylene glycol monobutyl ether and propylene glycol butyl ether.
5. The water-based acrylic emulsified asphalt anticorrosive coating according to claim 1, characterized in that: The filler includes at least one of heavy calcium, titanium dioxide and barium sulfate.
6. The water-based acrylic emulsified asphalt anticorrosive coating according to claim 1, characterized in that: The defoamer B includes a polyether defoamer, the wetting agent includes lauryl alcohol polyoxyethylene ether, and the preservative includes a Kathon preservative.
7. The water-based acrylic emulsified asphalt anticorrosive coating according to claim 1, characterized in that: The pH regulator includes ammonia water with a mass percentage concentration of 48-50%, and the pH buffer includes at least one of sodium bicarbonate and sodium carbonate.
8. The water-based acrylic emulsified asphalt anticorrosive coating according to claim 1, characterized in that: The initiator includes at least one of sodium persulfate, potassium persulfate, and ammonium persulfate; the oxidant includes at least one of tert-butyl hydroperoxide and hydrogen peroxide; and the reducing agent includes at least one of sodium pyrosulfite and ascorbic acid.
9. A method for preparing the aqueous acrylic emulsion according to any one of claims 1 to 8, characterized in that: The following steps are involved: S001. First, add 18 parts of deionized water to the emulsification tank, then add acrylic acid, methacrylic acid, pH buffer and 0.6 parts of anionic emulsifier to the emulsification tank, adjust the stirring speed to 200-300 rpm / min, and continue stirring for 8-10 minutes; S002. After the stirring in step S001 is completed, the stirring speed is adjusted to 300-400 rpm / min, and butyl propylene, methyl methacrylate, styrene, isooctyl acrylate, and glycidyl methacrylate are added to the emulsification tank in sequence, and stirring is continued until a smooth and stable pre-emulsion is obtained; S003. 0.1 parts of the initiator were added to 0.9 parts of deionized water and fully dissolved to obtain an initiator solution A; S004. 0.3 parts of the initiator were added to 5.7 parts of deionized water and fully dissolved to obtain an initiator solution B; S005. 0.02 parts of the oxidant are added to 0.18 parts of deionized water and fully dissolved to obtain an oxidant solution; S006. 0.02 parts of the reducing agent are added to 0.18 parts of deionized water and fully dissolved to obtain a reducing agent solution; S007. Add 25 parts of deionized water to the reactor, heat the reactor to 65-75°C, add 0.04-0.06 parts of anionic emulsifier to the reactor, and stir for 8-12 minutes; S008. After the stirring in step S007 is completed, the reactor is heated to 85-87°C, and then 5% of the total weight of the pre-emulsion is added to the reactor, and the initiator solution A is immediately added for seeding; S009. Observe the temperature of the reactor. When the temperature of the reactor is at 88°C, the remaining pre-emulsion and initiator solution B are added dropwise to the reactor. During the addition, the temperature of the reactor is controlled at 85 to 88°C. S010. After the initiator solution B and the pre-emulsion are added, the reactor is kept warm for 58 to 62 minutes. After the insulation is completed, the reactor is cooled to 65 to 70°C, and then the oxidant solution and the reducing agent solution are added simultaneously; S011. After the oxidant solution and the reductant solution are added dropwise, the reactor is kept warm for 8 to 12 minutes. After the insulation is completed, the reactor is cooled to 50°C, and then a pH adjuster, 1.0 to 2.0 parts of deionized water, a wetting agent, a preservative, and a defoaming agent are added in sequence. The mixture is stirred for 4 to 6 minutes and then filtered to obtain an aqueous acrylic emulsion.
10. A method for preparing a water-based acrylic emulsified asphalt anti-corrosion coating, characterized in that: The following steps are involved: T001. Add deionized water, neutralizer, dispersant, defoamer and filler to the grinder in order, grind until the fineness of the mixed liquid is less than 30um, and then add water-based acrylic emulsion and film-forming aid to the mixed liquid; T002. After the water-based acrylic emulsion and the film-forming aid are added to the mixture, the mixture is stirred in a high-speed disperser for 10 to 12 minutes, and the speed of the high-speed stirrer is controlled at 780 to 820 rpm / min; T003. After the stirring of step T002 is completed, continue to add anionic emulsified asphalt, leveling agent, anti-rust agent, and thickener to the mixed liquid. The speed of the high-speed mixer is controlled at 1500-1800 rpm / min. After stirring for 18-20 minutes, a water-based acrylic emulsified asphalt anti-corrosion coating is obtained.
Citation Information
Patent Citations
Acrylic ester copolymer emulsion used for high-water-resistance heavy anti-corrosion coating and preparation method thereof
CN105153828A
Modified asphalt and preparation method thereof
CN108178933A
Waterborne acrylic anticorrosive coating containing asphalt and preparation method thereof
CN109054519A
Single-component water-based non-cured rubber asphalt waterproof paint and production method thereof
CN110643284A
Single-component water-based high-solid-content high-elastic creep rubber asphalt waterproof coating and preparation method thereof
CN110713795A